Intrageneric evolutionary timing and hidden genetic diversity of Paramecium lineages (Ciliophora: Oligohymenophorea). Issue 7 (28th August 2020) - De Souza, Bianca Aline; Dias, Roberto Junio Pedroso; Senra, Marcus Vinicius Xavier
Abstract : Members of the genus Paramecium (Ciliophora, Oligohymenophorea) are widespread ciliates able to colonize many fresh, brackish and marine water environments around the globe. Despite they have been historically used in a variety of research fields, ranging from genomics to ecology, their evolutionary origin and genetic structure remains elusive for most valid species. There are currently 19 valid species distributed in 5 subgenera, which can have restricted to cosmopolitan distribution patterns. However, their true biodiversity and biographical distribution are blurred by evidences of cryptic species within most of these valid species. Here, we inferred a 18S rDNA-based time-calibrated tree to determine the evolutionary origin of extant Paramecium lineages and intra-genus phylogenetic relationships. Next, we used two common computational species delimitation algorithms (PTP and mPTP) to analyze a population-level (cytochrome oxidase subunit I [COI]) phylogeny to predict the existence of independent evolutionary unities (IEUs) within valid Paramecium morphospecies. Our data suggest that, some cosmopolitan Paramecium may have emerged prior to the Cretaceous period (before the complete separation of the continents), thus, explaining their wide distribution pattern. We found that the diversity of cryptic species may be higher than previous though and that most of the valid Paramecium species should be, in fact considered as complexes of species, composed each by IEUs that can co-occur within restricted or wide geographical areas. Moreover, our data indicate that these species delimitation algorithms (PTP and mPTP) may be of great assistance to uncover the diversity of cryptic species within Paramecium (or any other microeukaryote) by indicating potential candidates for more in detail future studies of taxonomists through integrative taxonomy frameworks.